2016
DOI: 10.1155/2016/7071907
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress in Out-Patients Assessed for Chronic Pain Compared to Those with Rheumatoid Arthritis

Abstract: Background. Patients diagnosed with chronic pain (CP) and rheumatoid arthritis (RA) represent two samples with overlapping symptoms, such as experiencing significant pain. Objectives. To compare the level of psychological distress among patients diagnosed CP attending a specialist pain clinic with those attending a specialist RA clinic. Measures. A cross-sectional study was conducted at an academic specialist chronic pain and rheumatology clinic. Participants. 330 participants included a CP group (n = 167) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 34 publications
(20 reference statements)
1
20
0
Order By: Relevance
“…Some studies have described changes in the incidence of oral diseases in MS patients, as is the case of the study by Castro et al. , who found that these patients are more likely to experience more caries compared to nonsyndromic, normoreactive individuals . Moreover, a study by Mussi et al.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Some studies have described changes in the incidence of oral diseases in MS patients, as is the case of the study by Castro et al. , who found that these patients are more likely to experience more caries compared to nonsyndromic, normoreactive individuals . Moreover, a study by Mussi et al.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have sought to relate MS to the autism spectrum disorder, whereas others have raised the possibility that social stigmatization, constant teasing, and bullying perpetrated by people in the same social circle, leading the own patient to become isolated, may work as adjuvants in the development of low selfesteem, behavioral problems, and psychiatric disorders. 15,16 The literature reports that psychological stress, anxiety, and depression are factors contributing to the development and impairment in autoimmune diseases. 16,17 Systemic lupus erythematosus (SLE) is an autoimmune disease with higher prevalence in adult women.…”
Section: S Y S T E M I C L U P U S E R Y T H E M a T O S U S A N D M mentioning
confidence: 99%
See 3 more Smart Citations